2015
DOI: 10.1111/fcp.12097
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of Src family kinases and therapeutic implications of their modulators

Abstract: Src family kinases (SFKs), the largest family of nonreceptor tyrosine kinases, include 10 members. Src was the first gene product discovered to have intrinsic protein tyrosine kinase activity. Src is widely expressed in many cell types and can have different locations within a cell; the subcellular location of Src can affect its function. Src can associate with cellular membranes, such as the plasma membrane, the perinuclear membrane, and the endosomal membrane. SFKs actions on mammalian cells are pleiotropic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 114 publications
(218 reference statements)
1
22
0
1
Order By: Relevance
“…PP1 was identified as a high-potency inhibitor of Fyn and acts as a competitive inhibitor of ATP binding. Currently, both AZD0530 and PP1 are mainly under investigation for the treatment of solid tumours, lung cancer and Alzheimer’s disease 32. In this study, we have demonstrated that OA progression can be prevented by targeting Fyn with these two inhibitors.…”
Section: Discussionmentioning
confidence: 62%
“…PP1 was identified as a high-potency inhibitor of Fyn and acts as a competitive inhibitor of ATP binding. Currently, both AZD0530 and PP1 are mainly under investigation for the treatment of solid tumours, lung cancer and Alzheimer’s disease 32. In this study, we have demonstrated that OA progression can be prevented by targeting Fyn with these two inhibitors.…”
Section: Discussionmentioning
confidence: 62%
“…In its inactive form, the end carboxyl-terminal Tyr527 residue is phosphorylated by protein tyrosine kinase Csk. Dephosphorylation at this level induces a conformational change in the protein, allowing the autophosphorylation of Tyr at residue 419, which is present in the activation loop, promoting and activating Src kinase (p-Src) [17, 18]. In normal basal conditions, 90-95% of Src es found in its inactive conformation.…”
Section: Introductionmentioning
confidence: 99%
“…Ponatinib did not reduce net levels of ABL phos-phorylation in merlin-deficient HSC (Figure 2A ). Ponatinib induced a dose-dependent increase in the total SRC protein level but did not alter the levels of the other SRC family members, FYN and YES, that play important roles in SC biology as well (Figure 2B ) [ 22 , 23 ]. We found a slight increase in SRC-Tyr416 phosphorylation in merlin-deficient HSC treated with 0.3 to 3μM (with a peak at 1μM).…”
Section: Resultsmentioning
confidence: 99%